GRAMD1/ASTER‐mediated cholesterol transport promotes Smoothened cholesterylation at the endoplasmic reticulum. (16th December 2022) - Qiu, Zhi‐Ping; Lin, Zi‐Cun; Hu, Ao; Liu, Yuan‐Bin; Zeng, Wan‐Er; Zhao, Xiaolu; Shi, Xiong‐Jie; Luo, Jie; Song, Bao‐Liang
Abstract: Hedgehog (Hh) signaling pathway plays a pivotal role in embryonic development. Hh binding to Patched1 (PTCH1) derepresses Smoothened (SMO), thereby activating the downstream signal transduction. Covalent SMO modification by cholesterol in its cysteine‐rich domain (CRD) is essential for SMO function. SMO cholesterylation is a calcium‐accelerated autoprocessing reaction, and STIM1‐ORAI1‐mediated store‐operated calcium entry promotes cholesterylation and activation of endosome‐localized SMO. However, it is unknown whether the Hh‐PTCH1 interplay regulates the activity of the endoplasmic reticulum (ER)‐localized SMO. Here, we found that PTCH1 inhibited the COPII‐dependent export of SMO from the ER, whereas Hh promoted this process. The RRxWxR amino acid motif in the cytosolic tail of SMO was essential for COPII recognition, ciliary localization, and signal transduction activity. Hh and PTCH1 regulated cholesterol modification of the ER‐localized SMO, and SMO cholesterylation accelerated its exit from ER. The GRAMD1/ASTER sterol transport proteins facilitated cholesterol transfer to ER from PM, resulting in increased SMO cholesterylation and enhanced Hh signaling. Collectively, we reveal a regulatory role of GRAMD‐mediated cholesterol transport in ER‐resident SMO maturation and Hh signaling. Synopsis: Cholesterol modification of Smoothened (SMO) is essential for Hedgehog signaling pathway activation. Here, cholesterol transport proteins GRAMD1s/ASTERs are shown to promote SMO cholesterylation in the endoplasmic reticulum (ER), thus accelerating its ER exit. SMO export from the ER is increased by Hedgehog and decreased by Patched1. The RRxWxR motif in the cytosolic tail of SMO is essential for its COPII recognition, ER exit, and ciliary localization. SMO cholesterylation promotes its export from the ER. GRAMD1/ASTER proteins transfer cholesterol from plasma membrane to ER and promote SMO cholesterylation. Abstract : Cholesterol modification promotes the activity of Hedgehog signaling component Smoothened by accelerating its COPII‐dependent ER exit.